2008
DOI: 10.1139/v07-155
|View full text |Cite
|
Sign up to set email alerts
|

A novel limonoid from the seeds of Chisocheton siamensis

Abstract: Analysis of an acetone/hexane (1:1) extract of the seeds of Chisocheton siamensis led to the isolation of a novel limonoid, chisosiamensin (1), along with five known limonoids, dysobinin (2), azadiradione (3), mohinin (4), epoxyazadiradione (5), and 6α -acetoxyepoxyazadiradione (6). Their structures were characterized by spectroscopic methods, including UV, IR, NMR, and MS. All isolated limonoids were reported for the first time as secondary metabolites of C. siamensis.Résumé : L'analyse d'un extrait par un mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…The genus Chisocheton, belong to family Meliaceae, consisting more than 50 plants and distributes in Nepal, India, Myanmar, China, Thailand, Indonesia, Malaysia, and Papua New Guinea (Vossen and Umali, 2002). Previous investigation of chemical constituents on Chisocheton plants had reported contain sesquiterpenoids (Phongmaykin et al, 2008), dammarane-type triterpenoids (Phongmaykin et al, 2008;Inada et al, 1993), lanostane-type triterpenoid (Katja et al, 2017a), tirucallane-type triterpenoids (Zhang et al, 2012) apo-tirucallane-type triterpenoids (Zhang et al, 2012;Yang et al, 2011), euphane-type triterpenoids (Supratman et al, 2019); limonoids (Maneerat et al, 2008;Laphookhieo et al, 2008;Mohamad et al, 2009;Yang et al, 2009;Najmuldeen et al, 2011;Wong et al, 2011;Nurlelasari et al, 2017;Supriatno et al, 2018), steroids (Najmuldeen et al, 2011) and phenolics (Inada et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Chisocheton, belong to family Meliaceae, consisting more than 50 plants and distributes in Nepal, India, Myanmar, China, Thailand, Indonesia, Malaysia, and Papua New Guinea (Vossen and Umali, 2002). Previous investigation of chemical constituents on Chisocheton plants had reported contain sesquiterpenoids (Phongmaykin et al, 2008), dammarane-type triterpenoids (Phongmaykin et al, 2008;Inada et al, 1993), lanostane-type triterpenoid (Katja et al, 2017a), tirucallane-type triterpenoids (Zhang et al, 2012) apo-tirucallane-type triterpenoids (Zhang et al, 2012;Yang et al, 2011), euphane-type triterpenoids (Supratman et al, 2019); limonoids (Maneerat et al, 2008;Laphookhieo et al, 2008;Mohamad et al, 2009;Yang et al, 2009;Najmuldeen et al, 2011;Wong et al, 2011;Nurlelasari et al, 2017;Supriatno et al, 2018), steroids (Najmuldeen et al, 2011) and phenolics (Inada et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies on Chisocheton plants reported the presence of compounds with interesting biological activities including sesquiterpenoids [2], dammarane-type triterpenoids [2,3], tirucallane-type triterpenoids [4], apo-tirucallane-type triterpenoids [4,5], limonoids [6][7][8][9][10][11], steroids [10], and phenolics [3].…”
Section: Introductionmentioning
confidence: 99%
“…Proton metin pada δH 2,84 dan 7,40 (H-17) saling terjodoh dua ikatan ( 2 J) dengan karbon metilen pada C-16 (δC 33,6) dan karbon kuarterner pada C-13 (δC 47,9) dan C-20 (δC 125,5) menyarankan posisi gugus furan terikat pada C-17. Perbandingan data NMR disobinin dengan senyawa limonoid yang ditemukan pada C. siamensis (Laphookhieo et al, 2008) menunjukkan kesesuaian yang tinggi, sehingga dengan demikian diidentifikasikan sebagai disobinin. Senyawa disobinin diuji aktivitas antimalaria terhadap P. falciparum galur 3D7 dengan nilai 0,001-0,01µg/mL.…”
Section: Hasil Dan Pembahasanunclassified